2010
DOI: 10.1002/glia.20967
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant astroglial atrophy and astrogliosis in a triple transgenic animal model of Alzheimer's disease

Abstract: Astrocytes are fundamental for brain homeostasis and are at the fulcrum of neurological diseases including Alzheimer's disease (AD). Here, we monitored changes in astroglia morphology throughout the age-dependent progression of AD. We used an immunohistochemical approach that allows us to determine the domain of glial cytoskeleton, by measuring the surface, volume, and the relationship between astrocytes and neuritic plaques. We investigated astroglia in the hippocampus of a triple transgenic mouse model of AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
341
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 423 publications
(392 citation statements)
references
References 50 publications
31
341
1
1
Order By: Relevance
“…This atrophic appearance remains in later ages (12 months), distinguished by developed Ab plaques and NFTs, which are confirmed by the immunoreactivity of Ab and phosphorylated tau protein (Supplementary Figure S1 at http://www.asnneuro.org/an/ 003/an003e071add.htm; Oddo et al, 2003b;Rodríguez et al, 2009b). Consistent reduction in the GFAP expression is in agreement with our previous observations of generalized atrophy of astrocytes in the HC, which similarly appear before the neuropathological marks (from 9 months) and are sustained in later ages (up to 18 months; Rodríguez et al, 2009b;Olabarria et al, 2010). Although some post-mortem studies have revealed hypertrophic astrocytes, characteristic of astrogliosis in the EC of AD human patients (Muramori et al, 1998;Porchet et al, 2003, Vanzani et al, 2005, this is only related to intralaminar astrocytes, since interlaminar astrocytes also showed disrupted processes and dynamic properties (Colombo et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This atrophic appearance remains in later ages (12 months), distinguished by developed Ab plaques and NFTs, which are confirmed by the immunoreactivity of Ab and phosphorylated tau protein (Supplementary Figure S1 at http://www.asnneuro.org/an/ 003/an003e071add.htm; Oddo et al, 2003b;Rodríguez et al, 2009b). Consistent reduction in the GFAP expression is in agreement with our previous observations of generalized atrophy of astrocytes in the HC, which similarly appear before the neuropathological marks (from 9 months) and are sustained in later ages (up to 18 months; Rodríguez et al, 2009b;Olabarria et al, 2010). Although some post-mortem studies have revealed hypertrophic astrocytes, characteristic of astrogliosis in the EC of AD human patients (Muramori et al, 1998;Porchet et al, 2003, Vanzani et al, 2005, this is only related to intralaminar astrocytes, since interlaminar astrocytes also showed disrupted processes and dynamic properties (Colombo et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…Recently, we reported the concomitant occurrence of astroglial atrophy and astrogliosis in the HC of the transgenic mice model of AD. The atrophy appears as a generalized process, whereas astrogliosis was triggered by developing SPs and Ab aggregates (Rodríguez et al, 2009b;Heneka et al, 2010;Olabarria et al, 2010;Verkhratsky et al, 2010;Rodríguez and Verkhratsky, 2011). In the present paper, we extended our analysis of AD-associated changes in astroglia to the EC.…”
Section: Introductionmentioning
confidence: 69%
“…before considerable accumulation of extracellular β-amyloid and formation of senile plaques) and they were characterised by decreased complexity of astrocytes (which had less primary and secondary processes) and by reduction on the size of profiles of astrocytes labelled with antibodies against GFAP or glutamine synthetase. [99,100,103,104]. The atrophic changes in astrocytes developed in a particular spatio-temporal pattern with the earliest signs of atrophy observed in the entorhinal cortex (at 1 months of age); at 3 months of age morphological atrophy of astrocytes was identified in the prefrontal cortex, whereas in the hippocampus the atrophic changes were evident from 9 to 12 months of age [99,100,103].…”
Section: Astroglia In Admentioning
confidence: 98%
“…Astroglial reactivity was not uniform throughout the brain; formation of extracellular β-amyloid deposits and emergence of senile plaques failed to induce reactive astrogliosis in entorhinal and prefrontal cortices [99,100]. In the triple transgenic (3xTG) AD mice over-expressing mutant genes for amyloid precursor protein (APP Swe ), presenilin 1 (PS1 M146V ) and microtubule-associated protein Tau (Tau P301L ), [101]and in PDAPP-J20 mice carrying the Swedish and Indiana human mutations of APP [102] astroglial atrophy was identified throughout the brain [99,100,[103][104][105][106]. Astrodegenerative changes were found at the early pre-symptomatic stages (i.e.…”
Section: Astroglia In Admentioning
confidence: 99%
“…In particular, synaptic strength and synaptic maintenance can be influenced by the neuroglia that structure the brain parenchyma, form the neuronal-vascular unit and provide a physical and functional cover for the majority of synapses in the CNS. Experiments on a triple-transgenic model of AD (mice expressing APP swe , PS1M146V and tauP301L; and thus developing both senile plaques and intraneuronal tangles [10,11] ) identified early astroglial atrophy [12,13] . This atrophy of astrocytes can cause reduced synaptic cover- age, which, in turn, may result in both impaired synaptic transmission and loss of synapses.…”
mentioning
confidence: 99%